Tingkat penerimaan penggunaan jamu sebagai alternatif penggunaan obat modern pada masyarakat ekonomi rendah-menengah dan atas - Andriati Andriati; R M Teguh Wahjudi (Faculty of Social and Political Science, Universitas Airlangga, 2016)
Herbs have become an important cultural heritage from Indonesia, as the consumption of herbs increased into 50%. This research is particularly important to analyze health quality of society through herbs as alternative of modern medicine to lower, middle, upper-social class group. The research problem addressed is how is the acceptance level of herb as alternative of modern medicine to middle, lower and upper class society in East Java. After finding the acceptance level of lower, middle, and upper class group toward herb usage, further analysis was focused on herbs management model in order to enhance society's health quality. Analysis unit in this research are society and bureaucracy. Informant was chosen by purposive sampling method (for keyinformants) and snowball method for complementary informant. Data was analyzed using qualitative technique. The research shows that the use of herbs as alternative of modern medicine in lower-middle class group was relatively high (58 %). The local government have a strategic role in managing herbs through policy innovation for health service in the local community. There is also an urgency to conduct a guidance, research, tax reduction, a more sophisticated method of herbal plant cultivation, herbs standardization, and strict supervision for herbs usage.